Degradation of petroleum refinery wastewater by using fenton reagent - Adzdzin Shafwan Bin Adlan (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
In this modern and global society, industrial wastewater remediation symbolizes binding problem which need certain understanding and unique solutions. In this research, an extensive experimental study of Fenton oxidation is needed, it is to understand the most suitable and optimal operative conditions in order to be implemented in the real industrial wastewater treatment. The research is carried out to analyze the heavy metal removal from untreated petroleum refinery wastewater. The analysis by Atomic Absorption Spectrometry (AAS) shows significant amount of heavy metal removal, assessing the removal efficiency of the process.